An integrated solution for 3D overhead cranes: Time-optimal motion planning, obstacle avoidance, and anti-swing - Van Chung Nguyen; Hue Luu Thi; Hoa Bui Thi Khanh; Huy Nguyen Danh; Dai Pham Duc; Tung Lam Nguyen (Engineering Science and Technology, an International Journal)
This paper proposed a motion planning scheme, a nonlinear controller integrated with an observer for a three-dimensional overhead crane (3DOC) nonlinear system. The designed motion planning considering system constraints and providing time-optimal, collision-free navigation in three dimensions is presented. Furthermore, the 3DOC system is characterized as a highly nonlinear, uncertain system and is always heavily influenced by external disturbances, the system variables are also partially measured using sensors. To solve all these problems, a second-order sliding controller (SO-SMC) based on an extended state observer (ESO) is formulated to solve the problem of uncertainty, disturbance, and furnishing a state estimation mechanism for the 3DOC nonlinear system. The closed-loop system, which consists of the extended state observer and the second-order sliding control stability, is verified via Lyapunov’s stability. Comprehensive simulations, experiments, and comparisons with existing methods are conducted under four cases with the presence of obstacles to demonstrate the observer’s quality and showcase the effectiveness of the proposed methods.